(untitled) (Advances in Applied Biological Research, 2026)
In those under 20, the most common solid malignancies are brain tumours, which account for most of cancer-related deaths. By gathering information from institutional series, population-based studies, and case-control investigations done all throughout the world, this review examines the weight, incidence, and risk elements related with brain tumours in children and adolescents. Recent epidemiological data from countries like Finland, Canada, the United States, China, and Korea points to an annual incidence rate among young people ranging from 3.5 to 5. 1 case per 100,000, with the highest rates observed among youngsters aged 0 to 4. Among the most frequent tumour types are pilocytic astrocytoma, medulloblastoma, ependymoma, aberrant teratoid/rhabdoid tumours, and medulloblastoma. Studies show small local variations in the incidence of tumour types; germ cell tumours are somewhat more common in Asian populations and show a slight male bias. This review focuses on brain tumour in the young population it’s a subject of growing medical and public health concern, this evaluation emphasizes the essential need of continuous monitoring using national cancer registries, molecular tumour profiling and improved early detection and genetic testing initiatives. Understanding regional variances and risk factors for paediatric brain tumour patients can inform future studies, focused prevention campaigns, and improved survival and treatment outcomes. This information was gathered from reputable websites such as DOAJ (directory of open access journals), ERIC (education resources information centre), ScienceDirect, PubMed and google scholar. The diagram has taken from biorander while the graph, pie chart and flow chart are made in MS word.